Produzindo casas de papel: As engrenagens da securitização de ativos imobiliários residenciais no Brasil. - Marlon Altavini de Abreu; Everaldo Santos Melazzo; João Vitor de Souza Ferreira (Confins)
This article offers an analysis in the expansion of the financialization process from Brazilian Real State sector. It aims to contribute to the debate regarding the mechanisms which turn a physical asset, with low liquidity and high transaction cost, on an asset with high liquidity and free of barriers to its circulation, with emphasis on types of contracts and securitised debts subordinating indicators of housing production, combined with expectations of financial market gain and different real estate markets integration through standardization and compilation of real estate debts into a single securitization term. This applies to the geographical scale of the country and is focused on a particular financial instrument, the Real Estate Receivables Certificates (CRI), regulating the range of transformations that have come to integrate, structure and coordinate Brazilian real estate investments. The total amount of CRI issued between 2011 and 2016 is taken into account, pointing out not only the importance of Caixa Econômica Federal bank of Brazil but also the role of house financing agent. Thus, the location in gated housing areas are also detailed, further exploring the dimensions of product homogenization, spatial dissemination and territorial selectiveness which they gradually produce, sell and move these paper houses around.